The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12328-011-0226-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatohepatitis (NASH) after pancreaticoduodenectomy: association of pancreatic exocrine deficiency and infection

Abstract: Previous clinical study has demonstrated that 30-40% of patients undergoing pancreaticoduodenectomy (PD) developed hepatic steatosis. However, nonalcoholic steatohepatitis (NASH) is a little-known complication after PD. Recently we encountered two patients with PD who later developed NASH diagnosed by liver biopsy. Case 1 was a 79-year-old woman who underwent PD for intraductal papillary mucinous neoplasm (IPMN). She had postoperative severe diarrhea due to pseudomembranous enterocolitis. Severe liver dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…It has been suggested that malnutrition due to pancreatic exocrine insufficiency is a main cause of NAFLD after PD, because supplementation of high-dose pancreatic enzyme improves it. Previously, we hypothesized its mechanism as follows: pancreatic exocrine insufficiency after PD is associated with fat malabsorption, resulting in fatty acid deficiency, which leads to increased conversion of carbohydrates into fat (i.e., increased fat deposition) in the liver [6,7]. In the three patients who developed NAFLD after PD at our institution, daily stool fat excretion was examined 7 RPV remnant pancreatic volume days after cessation of pancreatic enzyme supplementation, revealing that it exceeded markedly the definition of steatorrhea as a daily excretion higher than 5-8 g: 45 g, 52 g and 68 g, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that malnutrition due to pancreatic exocrine insufficiency is a main cause of NAFLD after PD, because supplementation of high-dose pancreatic enzyme improves it. Previously, we hypothesized its mechanism as follows: pancreatic exocrine insufficiency after PD is associated with fat malabsorption, resulting in fatty acid deficiency, which leads to increased conversion of carbohydrates into fat (i.e., increased fat deposition) in the liver [6,7]. In the three patients who developed NAFLD after PD at our institution, daily stool fat excretion was examined 7 RPV remnant pancreatic volume days after cessation of pancreatic enzyme supplementation, revealing that it exceeded markedly the definition of steatorrhea as a daily excretion higher than 5-8 g: 45 g, 52 g and 68 g, respectively [16].…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, we reported the incidence of NAFLD after PD as 37.0% and revealed that NAFLD after PD was significantly associated with the following three factors: pancreatic adenocarcinoma, resection line, and postoperative diarrhea, suggesting the contribution of malnutrition due to pancreatic exocrine deficiency . We also encountered two patients with PD who later developed NASH confirmed by liver biopsy, in whom treatment of infectious complications and high‐dose pancreatic enzyme supplementation improved liver dysfunction and liver steatosis . The pathogenesis of NAFLD after PD may therefore differ from that of conventional NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Jaundice due to steatohepatitis following pancreatoduodenectomy is a rare occurrence [7, 8, 9, 10, 11]. Our patient progressed rapidly to liver failure and jaundice subsequent to NASH.…”
Section: Introductionmentioning
confidence: 80%
“…According to previous reports, non-alcoholic fatty liver disease and NASH following pancreatoduodenectomy can be improved by the administration of pancreatic enzymes [10]. After switching the patient's treatment from oral to intravenous zinc, serum zinc levels rose rapidly and ammonia levels declined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation